An overview of enzyme technology used in food industry - Aizi Nor Mazila, Ramli; Hong, Pui Khoon; Nor Hasmaliana, Abdul Manas; Nur Izyan, Wan Azelee (Elsevier, 2021)
For centuries, enzymes are playing profound roles in food processing and are extensively employed in food manufacturing. Devoted research continues perpetually to analyze enzyme-specific properties including their isolation, purification, and characterization. Advanced developments in the field of enzyme technology have developed new enzymes with wider applications and properties and different application capacities are still being explored. Typically, enzymes are obtained from animal, plant, or microbial sources and due to several benefits such as simple, economical, and consistent production, microbial enzymes are more preferable in several food preparations for improving food properties. The number of enzymes commercially used in food processing is increasing constantly and field of application will be expanded progressively in near future. This chapter aims to provide an overview in enzyme technology for food industries including its current development. The representative of enzymes used in food processing including the wide range of their application has been extensively discussed. In addition, various sources of enzyme for food processing applications have also been briefly addressed.